El arbitraje después del arbitraje - Castillo Freyre, Mario (2017)
In this article, the author analyzes the proceedings after the conclusion of the arbitration, in accordance with current regulations. Thus, it develops the possibilities that can be presented before the arbitral award can be firm and, the possibilities that exist after that.